The Precariat The New Dangerous Class - Standing, Guy (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This book presents the Precariat - an emerging class, comprising the rapidly growing number of people facing lives of insecurity, moving in and out of jobs that give little meaning to their lives. Guy Standing argues that this class is producing instabilities in society. Although it would be wrong to characterise members of the Precariat as victims, many are frustrated and angry. The Precariat is dangerous because it is internally divided, leading to the villainisation of migrants and other vulnerable groups. Lacking agency, its members may be susceptible to the siren calls of political extremism. To prevent a 'politics of inferno', Guy Standing argues for a 'politics of paradise', in which redistribution and income security are reconfi gured in a new kind of Good Society, and in which the fears and aspirations of the Precariat are made central to a progressive strategy.